Fenologia da copaíba (Copaifera langsdorffii Desf. -- Leguminosae, Caesalpinioideae) em uma floresta semidecídua no sudeste do Brasil - PEDRONI, FERNANDO (2002)
Plant phenology is concerned with the timing of recurring events, and is poorly known for tropical forest species, although this ecosystem has the greatest diversity of phenological patterns. A phenological study was carried out from February/1991 to April/1993. Thirty six trees were systematically observed biweekly for changes on leaf fall, leaf flushing, flowering and fruiting. Leaf fall and flushing were synchronized phases. These events always occurred at the end of dry season (leaf fall) and start of rainy season (leaf flushing) being clearly related with precipitation. The flowering occurred in the rainy season, and fruiting during the dry season. Fruiting did not show an annual cycle, but years which massive fruiting being followed by non productive years. Other non climatic factors, like seed dispersers and seed predators were also likely to affect fruiting.